Strategi Inovatif Pojok Perpustakaan Dan Rumah Pintar Dalam Pengembangan Pendidikan Formal Dan Non Formal Di Desa Penatarsewu Tanggulangin - Ragillia Fitri Nur Janah; Muhammad Fahrul Muttaqin; M. Alvan Rizki (Cv. Utility Project Solution, 2023)
Penatarsewu is a village in Tanggulangin sub-district, Sidoarjo district. Penatarsewu village is known as the smoke village. The geographical location of Penatarsewu village is densely populated, located quite far from the city center about 12.9 KM. The development of technology and education that is increasingly advanced is expected to help residents to use the facilities as well as possible. For this reason, we UMSIDA KKN-T Group 27 students provide assistance and innovate to help develop the level of understanding of education to the community, especially for minors. The innovation strategy provided is by opening a